Morphological and Genetic Evidence Confirmed Three New Records of Ghost Shark Species (Chimaeriformes) From the Andaman Sea of Thailand - Krajangdara, Tassapon; Fahmi; Ebert, David A.; Chaorattana, Chanikarn; Khudamrongsawat, Jenjit (Tropical Natural History, 2021)
Three species of ghost sharks (Chimaeriformes) were recorded for the first time from the Andaman Sea of Thailand during a deep-sea trawl survey conducted from October 1-15, 2018. Morphological characteristics primarily revealed species described as the sicklefin chimaera, Neoharriotta pinnata (Rhinochimaeridae), longspine chimaera, Chimaera aff. macrospina (Chimaeridae) and Philippine chimaera, Hydrolagus cf. deani (Chimaeridae). The presence of N. pinnata in the Andaman Sea of Thailand provided a plausible extension of its distributional range, but the record of the other two ghost sharks were far outside their known ranges and remained tentative. Using DNA barcoding, the Chimaera aff. macrospina sample was different from Australian C. macrospina and any other Chimaera species whose DNA sequences were available in databases. The sample of Hydrolagus cf. deani showed slight differences in morphology with the known H. deani, H. mitsukurii and H. africanus. It was close to H. africanus based on the genetic information, but state morphologically, especially shape of second dorsal fin, this specimen was most similar to H. deani.